1999
DOI: 10.1111/j.1745-4581.1999.tb00370.x
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR DETECTION AND IDENTIFICATION OF ASPERGILLUS NIGER CONTAMINATION IN COSMETIC/PHARMACEUTICAL RAW MATERIALS AND FINISHED PRODUCTS

Abstract: A PCR‐based assay using a one step sample preparation was developed and validated against standard methods for the rapid detection of Aspergillus niger contamination in cosmetic/pharmaceutical raw materials and finished products. Artificially contaminated samples were added to Sabouraud Dextrose Broth (SDB) with 10% Tween 20 and 3% Soy Lecithin. Samples were then agitated at 200 revolutions per minute for 24 h at 35C. Prior to the PCR assay, sample preparation consisted of adding 10 μL of the 24 h enrichment b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Other studies have showed that the presence of B. cepacia in products used for mouth hygiene has frequently been implicated in B. cepacia infection [29][30][31]. Contamination of cosmetics and pharmaceuticals with B. cepacia is also a frequent problem in the United States and it is a cause of major product recalls [32][33][34]. B. cepacia can cause diseases primarily among immuno-compromised populations [35].…”
mentioning
confidence: 99%
“…Other studies have showed that the presence of B. cepacia in products used for mouth hygiene has frequently been implicated in B. cepacia infection [29][30][31]. Contamination of cosmetics and pharmaceuticals with B. cepacia is also a frequent problem in the United States and it is a cause of major product recalls [32][33][34]. B. cepacia can cause diseases primarily among immuno-compromised populations [35].…”
mentioning
confidence: 99%
“…Similarly in the EU, recalls notified by the Rapid Alert System for non-food consumer products (RAPEX) between 2005 until week 17 in 2008 showed contamination by P. aeruginosa was also the most frequently identified microorganism in the 24 products recalled due to microbiological contamination [31]. Jimenez and Smalls [32] noted also that members of the genus Burkholderia, notably B. cepacia, are increasingly responsible for recall of products.…”
Section: Incident Historymentioning
confidence: 96%
“…Sie können bereits herstellerseitig kontaminiert sein und zu Ausbrüchen mit diesen Erregern füh-ren [4,15,20]. Dabei kommt auch Burkholderia-cepacia-Komplex (Bcc) als Kontaminant solcher Produkte in Betracht [13,17]. Dies sind gramnegative Bakterien, die v. a. in der Umwelt gefunden werden und als opportunistische Krankheitserreger vorkommen [17].…”
Section: Hintergrundunclassified